Phenotypic plasticity of metastatic melanoma - I. N. Mikhaylova; O. A. Аnurova; A. A. Lushnikova; I. V. Tsyganova; А. S. Senderovich; T. Т. Kondratieva; L. V. Demidov; N. N. Mazurenko (Сибирский онкологический журнал)
Introduction. Metastatic melanoma is characterized by clinical and morphological heterogeneity and plasticity. Rare cases of metastatic melanoma are known, that have no visual expression of melanocytic markers. Contradictory histology of such melanomas requires a differential diagnosis from morphologically similar non- melanocytic tumors, sarcoma or lymphoma. objective is to describe the extraordinary cases of metastatic melanomas with low expression of differentiation markers. material and methods. 15 melanoma cases with unusual clinical and morphological characteristics were included in the study. These tumors were examined by pathologist and cytologist, by immunohistochemical and FISH analyses, mutations in BRAF, NRAS and KIT genes were detected by PCR. results. Some primary tumors were amelanotic, therefore, they were difficult for differential tumor diagnosis. Most frequently, primary tumors were located on the back, shin or head. In 4 patients the primary focuses were not detected. Metastatic lesions were as large nodular tumors in soft tissues of the back or lower limb. Most tumors belong to mixed or spindle-cell histological types. Spindle-shaped cells were also revealed by cytological analysis. BRAF gene mutations were identified by genetic analysis in 27 % of tumors, NRAS and KIT gene mutations were not detected. In 4 cases FISH analysis was performed to detect EWSR1 gene rearrangements, but it did not confirm the diagnosis of sarcoma. conclusion. The results indicate the presence of a heterogeneous group of melanoma cases, which have a number of morphological and molecular features that bring them closer to sarcomas.